The Leadership Style Of Kh Budi Rahman Hakim Phd (Abah Jagat) In Increasing Teacher Motivation In Pesantren - Kurnia Nurafny, Reky; Safitri, Sundaniawati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
ABSTRACTThis research aims to describe and analyze leadership styles in enhancing teacher motivation. The research was conducted at Pondok Pesantren Jagat’ Arsy, with KH Budi Rahman Hakim, PhD (Abah Jagat) as the head of the Islamic boarding school as the research subject. Data were obtained through interviews, observations, and documentation. The data analysis technique in this study followed the following procedures: data reduction, data presentation, conclusion, and verification. The results of this research explain the leadership styles applied by Abah Jagat in enhancing teacher motivation, which involves one leadership style and, in certain aspects, different leadership styles. The dominant leadership styles applied are charismatic and transformational leadership, although, on the other hand, an authoritarian leadership style is also implemented. This is reinforced by the leadership functions applied by Abah Jagat and the forms of motivation provided following Maslow’s Need Hierarchy Theory: a) motivating teachers by fulfilling their physiological needs, b) creating motivation to fulfil teachers’ security needs, c) providing motivation by addressing teachers’ need for affection, d) providing motivation for teachers’ self-actualization needs.Keywords: Leadership Style, Work Motivation, Islamic Boarding School